Trame controluce. Il patriarca 'protestante' Cirillo Loukaris / Backlighting Plots. The 'Protestant' Patriarch Cyril Loukaris - NOSILIA, VIVIANA; PRANDONI, MARCO (Studi e saggi, 2015)
Cyril Loukaris (1570-1638), Orthodox patriarch of Alexandria and later of Constantinople, is a fascinating and controversial figure. In addition to being a religious authority, the patriarch proved to be a first-rate politician and diplomat, capable of weaving a vast network of relationships. An acute mediator between cultures, he was a prominent intellectual of his time. The volume, the first of its kind in Italy, collects contributions from scholars of different disciplines, which bring out the multiplicity of cultural and geopolitical plans and areas in which the "Protestant" patriarch Loukaris carried out his activity. For the variety of approaches and areas examined, the essays reflect the many-sided nature of this figure, of which an unpublished sermon and related documents from the Moscow State Archives are published.